Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

factorise x(x-a)-y(y-a)

Asked by Jayasree C 29th July 2012, 3:44 PM
Answered by Expert
Answer:
Answer : Given :  x(x-a)-y(y-a)
To factorise the above.
 
Let f(x) = x(x-a)-y(y-a)
=> f(x) = x- ax - y2+ ay
=> f(x) = x- y - ax + ay    { rearranging the quatities } 
=> f(x) =  ( (x - y)(x+y) )  - a ( x -y )    { using a2 - b2 = (a+b) (a-b) }
 
Take (x - y) common  , we get 
=> f(x) = (x - y) (x + y - a ) Answer
Answered by Expert 30th July 2012, 2:14 AM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!